Klasterisasi Lapangan Usaha Provinsi Kalimantan Tengah - Hartandy, Alfi Rizkiyanoor; Haida, Nanda Rizqa Nur; Haryadi, Rahmad; Putra, Dwi Ardi Wicaksana (Ecoplan, 2025)
The interaction between business sectors in Central Kalimantan Province exhibits potential spatial dependence. Economic activities in one region can influence economic dynamics in other districts/cities. This study aims to cluster 17 business sectors to identify patterns of spatial dependence among districts/cities in the region. This research analyzed data from the 2022 Gross Regional Domestic Product (GRDP) at Constant Prices by business sector for each district/city in Central Kalimantan Province. The analysis was conducted using the Moran's Index and Local Indicators of Spatial Association (LISA) approach, employing the Queen Contiguity spatial weight matrix through the Geoda software. The results indicate that not all economic sectors exhibit significant spatial dependence. Out of the 17 sectors analyzed, 14 show patterns of spatial dependence among districts/cities. Meanwhile, the remaining sectors do not exhibit strong spatial relationships. These dependency patterns suggest the potential for economic influence across regions. This potential can be leveraged for more effective development strategies. By understanding the clustering of economic sectors with spatial linkages, this study contributes to formulating economic development strategies based on inter-district collaboration. These findings are expected to serve as a foundation for regional economic policy planning to promote more inclusive and sustainable growth in Central Kalimantan Province.